LA ESFERA AFECTIVA EN LA EDUCACIÓN DE LOS MENORES SIN AMPARO FAMILIAR - Alybé Moreno-Aurioles Matamoros (University of Las Tunas, 2018)
El artículo aborda los principios y categorías que sustentan el tratamiento educativo en la atención a las necesidades educativas especiales originadas por el fenómeno desamparo familiar, desde la concepción de familia; se argumenta sobre los centros de asistencia social donde son atendidos los menores sin amparo familiar que deben cumplir con las funciones establecidas para la familia en nuestra sociedad. Se reflejan elementos que obligatoriamente deben tenerse en cuenta para favorecer el desarrollo de la esfera afectiva como las vivencias, actividad, educación, enfatizando en las características de esta esfera, base de la personalidad, unida a la cognitiva. ABSTRACT This work deals with the principles and categories that sustain the educative treatment in the attention of the especial educative needs coming from the homeless phenomenon. It tackles the essence from the family conception having in mind that in the social assisting centers where homeless children are assisted, the established functions for the family in our society should be fulfilled. They are reflected the elements that must be taken into account to favour the development of the educative sphere, such as living experiences, activity and actions, making emphasis in the characteristics of this sphere based into the cognitive constituents of the personality. Key words: homeless children education-affective sphere-spiritual-affective and educative function of the family.